Technical studies prepared for the Banking Commission - India (Republic).; Reserve Bank of India (Bombay : Reserve Bank of India, 1972)
The papers have been written with a limited objective in view: either to bring out some specific points or issues for consideration of the commission or to throw light on certain aspects or trends in the banking system.
Vol. 1: each section has special t.p.
Selection of the studies and reports on surveys sponsored by the Commission and of the papers prepared mainly by the staff of the Special Cell in the Reserve Bank of India to assist the Banking Commission.
Includes bibliographical references.
osc 08/06/2018
Loans
Keywords: Banks and banking